Quinuclidine ring-containing aldehyde monomer, suspension type polyaryl quinuclidine ring polymer, and preparation method and application of suspension type polyaryl quinuclidine ring polymer
By combining aldehyde monomers containing quinuclidine with aromatic main chains, suspended polyarylquinuclidine polymers are formed, which solves the degradation problem of anion exchange membranes in alkaline environments, achieves high chemical stability and improves mechanical properties, and is suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202411066741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-09-19
AI Technical Summary
Existing anion exchange membranes are easily degraded in alkaline environments, resulting in insufficient mechanical and chemical stability, which cannot meet the needs of large-scale industrial applications. Especially under high temperature and high concentration conditions, there are problems of perforation and degradation.
Quinuclidine-containing aldehyde monomers are combined with aromatic main chains to form suspended polyarylquinuclidine polymers, which are then quaternized to prepare ultra-high stability anion exchange membranes. The aldehyde groups are migrated to the outside of the quinuclidine ring to maintain its rigid structure. Combined with hydrophobic unit copolymerization and cross-linking agents, the chemical stability and mechanical properties are improved.
The anion exchange membrane has achieved high chemical stability, low water absorption and swelling rate, improved ion transfer rate and conductivity, and significantly improved long-term stability of the membrane in high-temperature alkaline environment, making it suitable for large-scale industrial applications.
Smart Images

Figure CN120665062A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water and fuel cells, and in particular to an aldehyde monomer containing quinuclidine, a hanging polyarylquinuclidine polymer, and a preparation method and application thereof. Background Art
[0002] Anion exchange membrane water electrolysis (AEM-WE) is one of the most promising technologies for the future hydrogen economy. By combining the advantages of alkaline water electrolysis (A-WE) and proton exchange membrane water electrolysis (PEM-WE) technologies, AEM-WE has the advantages of low cost and high efficiency, thus creating an economically viable and scalable electrolysis device for clean energy conversion and utilization. However, the development of AEM-WE is still in its early stages, especially due to the lack of key materials such as anion exchange polyelectrolytes and electrocatalysts, which leads to limited durability of the equipment. However, the large-scale industrialization and sustainable deployment of anion exchange membrane water electrolysis is believed to be due to the lack of ultra-high stability and high performance anion exchange membranes, such as those used in PEM-WEs. Membrane. In recent years, there has been great interest in developing and exploring new synthetic routes for anion exchange membranes that can be used in electrochemical energy storage and conversion devices such as metal-air batteries, redox flow batteries, and anion exchange membrane fuel cells. Anion exchange membranes for anion exchange membrane water electrolysis are composed of a polymer backbone, functional cationic groups, and free OH groups. - ions, where OH- ions balance the charge of the cationic groups. To achieve high-performance anion exchange membranes, a variety of polymer backbones, including poly(arylene ether), poly(norbornene), poly(benzimidazole), and ether-free poly(arylene), along with functional cationic groups such as ammonium, imidazole, quaternary phosphonium salts, and metallocenes, have been combined and explored. Unfortunately, these combinations do not address the issue of alkaline stability due to OH- attack, particularly since the arylene-linked backbones and benzyltrimethylammonium cations are susceptible to OH- attack.
[0003] In alkaline environment, polyarylpiperidine structures (PAPs) containing dimethylpiperidine (DMP) have three degradation pathways, including nucleophilic substitution of methyl groups at the equatorial bond (S N 2) Methylene S N2 and Hofmann elimination (E2) of β-H in a flat bond. Among them, E2 is considered to be the main degradation pathway. Especially in a high-concentration alkaline environment and high temperature (60-90°C) conditions, anion exchange membranes containing DMP are prone to chemical degradation and perforation. Since this degradation process is irreversible, long-term operation will reduce battery performance and cause electrode short circuits, ultimately leading to device failure. In addition, due to the rigid main chain, the conformational deformation and ring strain relaxation of the piperidine ring reduce the mechanical stability of PAP. At the same time, compared with the undeformed small molecule piperidine ring, the stability of the piperidine ring in PAP is greatly reduced. This makes the PAP series of anion exchange membranes face huge challenges when used under more severe working conditions. Therefore, it is necessary to explore and develop ultra-high stability quaternary ammonium salt structures to meet the needs of special application scenarios, especially in large-scale industrial applications.
[0004] In summary, the anion exchange membranes currently on the market still have structural defects, resulting in their relatively poor chemical stability, making them unable to meet the needs of special application scenarios, especially in large-scale industrial applications. Higher alkaline stability directly determines the durability and efficiency of anion exchange membrane water electrolysis, metal-air batteries, redox flow batteries, and anion exchange membrane fuel cell devices. Therefore, the relevant technology urgently needs to develop an anion exchange membrane with excellent mechanical strength, high ionic conductivity and ultra-high chemical stability to promote the large-scale production and industrialization of anion exchange membrane-related devices. Summary of the Invention
[0005] To this end, the first technical problem to be solved by the present invention is to provide an aldehyde monomer containing a quinuclidine ring, wherein the functional group connected to the electron-rich benzene ring, namely the aldehyde group, is migrated to the exocyclic position of the quinuclidine ring, so that the quinuclidine ring is suspended outside the aromatic main chain in the polymer, thereby avoiding destroying the rigid structure of the quinuclidine ring and maintaining its high symmetry, thereby showing its ultra-high stability function and further improving the anion transport rate and chemical stability.
[0006] The second technical problem to be solved by the present invention is to address the above-mentioned problems existing in existing anion exchange membrane structures. A suspended polyarylquinuclidine polymer and a quaternized suspended polyarylquinuclidine polymer are provided, along with respective preparation methods. The anion exchange membrane prepared from the suspended polyarylquinuclidine polymer and the quaternized suspended polyarylquinuclidine polymer thus exhibits low strain ring tension, high chemical stability, structural stability, and excellent electrical conductivity and ionic conductivity, further resolving the problem of chemical structural stability of the anion exchange membrane. Furthermore, by using a crosslinker or copolymerizing with a hydrophobic unit, the anion exchange membrane exhibits low water absorption and swelling rates, further improving the mechanical and electrical conductivity of the anion exchange membrane, thereby enabling the preparation of an anion exchange membrane with ultra-high stability.
[0007] The third technical problem to be solved by the present invention is to provide an ultra-high stability anion exchange membrane prepared based on an OH-type quaternized suspended polyarylquinuclidine polymer. The anion exchange membrane has ultra-high chemical stability, structural stability, excellent electrical conductivity and ionic conductivity, and has excellent performance in applications such as anion exchange membrane water electrolysis and anion exchange membrane fuel cells.
[0008] The fourth technical problem to be solved by the present invention is that the polymer solution can be used as an ionomer and mixed with a catalyst, alcohol, and water to form a catalyst ink, which can be used in the fields of water electrolysis, fuel cells, CO2 reduction, metal-air batteries, and flow batteries to realize ultra-high performance and ultra-high durability electrochemical devices.
[0009] The fifth technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned suspended polyarylquinuclidine polymer and anion exchange membrane.
[0010] As used herein, the term "halogen" may include fluorine, chlorine, bromine or iodine.
[0011] As used herein, the term "C1-C10 alkyl" refers to a monovalent substituent derived from a straight-chain or branched saturated hydrocarbon having 1 to 10 carbon atoms, examples of which include, but are not limited to, methyl, ethyl, propyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, and hexyl.
[0012] As used herein, the term "C1-C15 alkylene" refers to a monovalent substituent derived from a straight or branched chain saturated hydrocarbon having 1 to 50 carbon atoms, examples of which include, but are not limited to, methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene.
[0013] As used in the present invention, the term "C3-C30 cycloalkyl" refers to a group derived from a monocyclic hydrocarbon or a polycyclic hydrocarbon having 1 to 30 ring main chain carbon atoms, and the cycloalkane may include cyclopropyl, cyclobutyl, adamantyl, and the like.
[0014] In the present invention, aryl and arylene groups include monocyclic, polycyclic or condensed ring aromatic groups, and the rings may be interrupted by short non-aromatic units and may contain spiro structures. Aryl groups include but are not limited to phenyl, biphenyl, terphenyl, naphthyl, phenanthrenyl, anthracenyl, fluorenyl, spirobifluorenyl, etc., and arylene groups include but are not limited to phenylene, biphenylene, terphenylene, naphthylene, phenanthrenyl, anthracenyl, fluorenyl, spirobifluorenyl, etc.
[0015] In the present invention, the definition of the group defines the range of the number of carbon atoms, and the number of carbon atoms is any integer within the defined range. For example, a C6-C20 aromatic group represents an aromatic group, and the number of carbon atoms can be any integer within the range of 6-20, such as 6, 8, 10, 13, 15, 17 or 20.
[0016] The scheme adopted by the present invention is as follows:
[0017] The present invention provides an aldehyde monomer containing quinuclidine, wherein the aldehyde monomer containing quinuclidine has a structure shown in the following formula (A):
[0018]
[0019] Wherein, L is selected from a single bond or a C6-C20 arylene group; R is selected from a single bond or a C1-C15 alkylene group.
[0020] Preferably, L is selected from a single bond, phenylene, biphenylene, and naphthylene;
[0021] Preferably, R is selected from a single bond or a C1-C10 straight chain alkylene group;
[0022] Preferably, R is selected from a single bond, methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene;
[0023] Preferably, the quinuclidine-containing aldehyde monomer is selected from one of the following structures:
[0024]
[0025] It will be understood that in the present invention, when both L and R are single bonds, -LR- is also a single bond;
[0026] Understandably,
[0027]
[0028] They indicate that R is connected to the α, β and γ positions of the quinuclidine, respectively.
[0029] The present invention also provides a use of the above-mentioned quinuclidine-containing aldehyde monomer in the preparation of anion exchange membranes.
[0030] The present invention also provides a pendant polyarylquinuclidine polymer, wherein the pendant polyarylquinuclidine polymer comprises a unit having the following structure (P1):
[0031]
[0032] Ar2 is a linear structural monomer containing at least two phenyl groups;
[0033] The definitions of R and L are the same as those in claim 1;
[0034] Preferably, the pendant polyarylquinuclidine polymer comprises units having the following structures:
[0035]
[0036] Wherein, Ar1 is a structural monomer containing at least 3 phenyl groups;
[0037] R1 is a hydrophobic unit;
[0038] The definitions of R and L are the same as those in claim 1;
[0039] wherein the molar number of units of the structure of formula (P1) in the pendant polyarylquinuclidine polymer accounts for 50-99.9% of the total molar number of units of the structure of formula (P1), formula (P2) and / or formula (3) in the pendant polyarylquinuclidine polymer;
[0040] Preferably, when the pendant polyarylquinuclidine polymer comprises structural units of formula (P1) and structural units of formula (P2), the pendant polyarylquinuclidine polymer may be a random copolymer, an alternating copolymer, a block copolymer or a graft copolymer; wherein the main chain of the graft copolymer is composed of structural units of formula (P2);
[0041] Preferably, the pendant polyarylquinuclidine polymer has a structure as shown in the following formula (P):
[0042]
[0043] z, y n 、y m are the molar ratios of the units with the structures of formula (P2), formula (P1), and formula (P3) to the total structural units of the polymer, y n +y m +z=100%.
[0044] It can be understood that in the present invention, ----- indicates that the connected group may or may not exist.
[0045] It is understood that Ar1 is a structural monomer containing at least 3 phenyl groups; specifically, Ar1 is a structural monomer containing 3, 4 or 5 phenyl groups.
[0046] Optionally, Ar2 is selected from two phenyl-substituted C6-C12 aromatic hydrocarbons, two phenyl-substituted alkenes, two phenyl-substituted C1-C10 alkanes, two phenyl-substituted C5-20 heteroaromatic hydrocarbons, diphenyl ether, and two benzene ring-fused C6-C12 cycloalkanes.
[0047] Optionally, the degree of polymerization of the pendant polyarylquinuclidine polymer is 1-10,000.
[0048] Preferably, z is 0-30%, y n 60%-100%, y m 0%-50%;
[0049] Preferably, the structure of Ar1 is a planar or spatial structure formed by three or more phenyl groups connected;
[0050] Preferably, the cross-linking points provided by the three or more phenyl groups in the structural monomer in Ar1 are uniformly or symmetrically distributed in the plane or space structure;
[0051] Preferably, Ar1 is selected from at least one of the following structures:
[0052]
[0053] Preferably, the linear structural monomer containing at least two phenyl groups of Ar2 comprises 2-4 linearly connected substituted or unsubstituted benzene rings; wherein the substituent of the substituted benzene ring is selected from halogen, C1-C15 alkyl or C1-C15 alkoxy;
[0054] Preferably, the benzene rings are connected by single bonds, unsaturated bonds, or fused bonds;
[0055] Preferably, Ar2 comprises a diphenyl-substituted linear aromatic hydrocarbon;
[0056] Preferably, Ar2 is selected from at least one of the following structures:
[0057]
[0058] Wherein, R2 is selected from hydrogen or C1-C10 alkyl;
[0059] Preferably, R1 is selected from a hydrophobic unit comprising an electron-withdrawing group;
[0060] Preferably, R1 is selected from substituted or unsubstituted aromatic ring hydrophobic units, substituted or unsubstituted saturated aliphatic hydrophobic units, substituted or unsubstituted ketone hydrophobic units, substituted or unsubstituted aldehyde hydrophobic units;
[0061] Preferably, R1 is selected from a hydrophobic unit comprising at least one of trifluoromethyl, carbonyl, aldehyde, and pentafluorobenzene;
[0062] Preferably, R1 is selected from one of the hydrophobic units having the following structure:
[0063]
[0064] wherein R3 and R6 are selected from hydrogen, halogen, C1-C10 alkyl or trifluoroacetyl; R4 is selected from C1-C10 alkyl; R5 is selected from hydrogen, C1-C10 alkyl or C6-C12 aryl;
[0065] It is understandable that in the present invention Indicates the attachment site.
[0066] Preferably, the hydrophobic copolymer units are formed by reacting corresponding ketone or aldehyde monomers.
[0067] The present invention also provides a method for preparing the above-mentioned suspended polyarylquinuclidine polymer, comprising the following steps:
[0068] A structural monomer raw material containing at least three phenyl groups corresponding to Ar1, a linear structural monomer raw material containing at least two phenyl groups corresponding to Ar2, the aforementioned quinuclidine-containing aldehyde monomer, and a ketone or aldehyde raw material corresponding to the R1 hydrophobic unit are mixed in a first solvent, and then a polymerization reaction is carried out under the action of a first catalyst. The obtained viscous solution is added to a second solvent, and the precipitated product is collected, washed, and dried to obtain the pendant polyarylquinuclidine polymer;
[0069] Wherein, Ar1, Ar2, and R1 are defined the same as above.
[0070] Preferably, the molar ratio of the structural monomer raw material containing at least 3 phenyl groups corresponding to Ar1 to the linear structural monomer raw material containing at least two phenyl groups corresponding to Ar2 is (0-50): (100-50); and / or,
[0071] The molar ratio of the linear structure monomer raw material containing at least two phenyl groups corresponding to Ar2 to the above-mentioned quinuclidine-containing aldehyde monomer is 1:(1-1.5); and / or,
[0072] The molar ratio of the ketone or aldehyde raw material corresponding to the R1 hydrophobic unit to the above-mentioned quinuclidine-containing aldehyde monomer is (0-0.4):1; and / or,
[0073] The first solvent comprises at least one of dichloromethane, chloroform or tetrahydrofuran; and / or,
[0074] The second solvent comprises at least one of ethyl acetate, methanol, ethanol, ether, tetrahydrofuran or acetone; and / or,
[0075] The volume ratio of the first solvent to the second solvent is 1:(10-30); and / or,
[0076] The amount of the quinuclidine-containing aldehyde monomer added to the first solvent is 10-22.5 mmol per 10-15 mL of the first solvent; and / or,
[0077] The washing step includes a step of adding a first alkali solution for washing and a step of adding a first alkali solution for washing; and / or,
[0078] The first alkali solution comprises at least one of K2CO3, KOH, NaOH or NaHCO3 solution, preferably with a concentration of 0.5-2.0M; and / or,
[0079] The drying step includes a step of vacuum drying at 60-80°C; and / or,
[0080] The first catalyst includes trifluoroacetic acid and / or trifluoromethanesulfonic acid; wherein,
[0081] Preferably, the first catalyst is trifluoroacetic acid, and the molar ratio of the trifluoroacetic acid to the quinuclidine-containing aldehyde monomer is (1-2):1;
[0082] Preferably, the first catalyst is trifluoromethanesulfonic acid, and the molar ratio of the trifluoromethanesulfonic acid to the above-mentioned quinuclidine-containing aldehyde monomer is (10-20):1.
[0083] The present invention also provides a quaternized pendant polyarylquinuclidine polymer, wherein the quaternized pendant polyarylquinuclidine polymer has a structure shown in the following formula (Q):
[0084]
[0085] Wherein, R7 is a quaternized group;
[0086] Preferably, R7 is a C1-C20 alkyl group with a quaternized structure;
[0087] Preferably, R7 is a C1-C20 alkyl group with a quaternized structure;
[0088] Among them, Ar1, Ar2, R1, z, y n 、y m The definitions of , R, and L are the same as above.
[0089] The present invention also provides a method for preparing the aforementioned quaternized pendant polyarylquinuclidine polymer, comprising the following steps: adding the aforementioned pendant polyarylquinuclidine polymer or the prepared pendant polyarylquinuclidine polymer to a third solvent, carrying out a quaternization reaction with a compound having an X-R7 structure under the action of a second catalyst; after the reaction, adding the viscous solution to a fourth solvent; collecting the precipitate, washing it, and drying it to obtain the quaternized pendant polyarylquinuclidine polymer; wherein X represents a halogen, and R7 has the same meaning as above; the aforementioned pendant polyarylquinuclidine polymer or the prepared pendant polyarylquinuclidine polymer is referred to as polymer P;
[0090] Preferably, the polymer P and the compound having the structure X-R7 are added in a ratio of 1:(1-3), with the ratio unit being g:mL; and / or,
[0091] The mass ratio of the polymer P to the second catalyst is (2-3):1; and / or,
[0092] The second catalyst comprises K2CO3; and / or,
[0093] The addition ratio of the polymer P and the third solvent is 1:(10-20), and the ratio unit is g:mL; and / or,
[0094] The third solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; and / or,
[0095] The fourth solvent comprises at least one of ethyl acetate, methanol, ethanol, acetone or diethyl ether; and / or,
[0096] The volume ratio of the third solvent to the fourth solvent is 1:(6-10); and / or,
[0097] The quaternization reaction temperature is 40-60° C. and the reaction time is 6-24 hours; and / or,
[0098] The drying step includes vacuum drying at 60-80°C.
[0099] The present invention also provides an ultra-high stability anion exchange membrane, wherein the material of the anion exchange membrane is OH - Type anion exchange membrane, the ultra-high stability anion exchange membrane has a structure shown in the following formula (T):
[0100]
[0101] Among them, Ar1, Ar2, R1, z, y n 、ym The definitions of , R, and L are the same as above.
[0102] The present invention also provides a method for preparing the above-mentioned ultra-high stability anion exchange membrane, comprising the following steps:
[0103] The quaternized pendant polyarylquinuclidine polymer or the quaternized pendant polyarylquinuclidine polymer prepared by the preparation method described above is mixed with a fifth solvent to obtain a mixture, and the mixture is cast on a substrate surface to obtain an initial polymer film; then, the initial polymer film is immersed in a second alkaline solution to obtain the ultra-high stability anion exchange membrane, wherein the quaternized pendant polyarylquinuclidine polymer or the quaternized pendant polyarylquinuclidine polymer prepared by the preparation method described above is denoted as polymer Q;
[0104] Preferably, the addition ratio of the polymer Q to the fifth solvent is 1:(10-100), and the addition ratio is g:mL; and / or,
[0105] The fifth solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; and / or,
[0106] The thickness of the high-stability anion exchange membrane is 20-60 μm; and / or,
[0107] The second alkali solution includes NaOH and / or KOH solution;
[0108] Preferably, the concentration of the second alkali solution is 0.5-2.0M; and / or,
[0109] The temperature of the impregnation step is 25-80° C., and the impregnation time is 8-12 hours.
[0110] Optionally, the preparation method further includes: a step of storing the ultra-high stability anion exchange membrane in deionized water with a protective atmosphere.
[0111] The present invention also provides the use of the ultra-high stability anion exchange membrane described above or the ultra-high stability anion exchange membrane prepared by the above-mentioned preparation method in alkaline water electrolyzers, anion exchange membrane electrolyzers, alkaline fuel cells, liquid flow batteries, and metal-air battery equipment.
[0112] The present invention also provides the use of the above-mentioned suspended polyarylquinuclidine polymer or the above-mentioned quaternized suspended polyarylquinuclidine polymer in the preparation of anion exchange membranes, anion membranes coated with a catalytic layer, and gas diffusion electrodes.
[0113] Beneficial effects of the present invention:
[0114] The present invention provides an aldehyde monomer containing a quinuclidine ring. In the monomer, the functional group connected to the electron-rich benzene ring, namely the aldehyde group, is migrated to the exocyclic position of the quinuclidine ring, so that the quinuclidine ring is suspended outside the aromatic main chain in the polymer. This avoids destroying the rigid structure of the quinuclidine ring and maintains its high symmetry, thereby demonstrating its ultra-high stability function and further improving the anion transport rate and chemical stability.
[0115] Furthermore, the suspended polyaryl quinuclidine polymer of the present invention adopts a full carbon chain skeleton structure, and by migrating the functional group aldehyde nitrogen-containing heterocycle connected to the electron-rich benzene ring to the α position, β position and γ position or / and outside the quinuclidine, the quinuclidine is suspended outside the aromatic main chain in the polymer, avoiding destruction of the rigid structure of the quinuclidine, maintaining its own ultra-high chemical stability, and further improving the anion transport rate. The polymer structure is modified by using strategies such as copolymerization with hydrophobic units, hyperbranching, and cross-linking to form a polymer with an ultra-high stable chemical structure. The suspended polyaryl quinuclidine polymer of the present invention has a low water absorption rate and swelling rate, further improving the mechanical stability and electrical conductivity of the anion exchange membrane, and has shown high performance and stability in tests of anion exchange membrane water hydrolysis and anion exchange membrane fuel cell.
[0116] Furthermore, the suspended polyarylquinuclidine polymer of the present invention is obtained by introducing a hydrophobic structural unit R1 to obtain a suspended polyarylquinuclidine copolymer, which adjusts the IEC of the polymer, thereby changing the water absorption rate (<25%) and swelling rate (<10%) of the anion exchange membrane, thereby improving the mechanical strength and mechanical properties of the polymer.
[0117] Furthermore, the pendant polyarylquinuclidine polymers described in the present invention, by introducing a bulky, rigid, hydrophobic monomer structure with cross-linking points, have been synthesized into a series of polymers with stable chemical structures. These polymers have a larger free volume, making the chains more mobile and the cationic groups more likely to aggregate during microphase separation, thus facilitating the establishment of ion channels with low transport resistance. This type of membrane has a conductivity of 60.11 mS cm at room temperature. -1 Compared with the common linear structure anion exchange membrane QPTP, the conductivity at room temperature is only 20.60mS cm -1 , the electrical conductivity performance of the membrane has been greatly improved.
[0118] Furthermore, the ultra-high stability anion exchange membrane of the present invention is based on the quaternized suspending polyarylquinuclidine polymer formed by the suspending polyarylquinuclidine polymer, which is then alkalized to form OH -This type of anion exchange membrane exhibits ultra-high chemical and structural stability, as well as excellent electrical and ionic conductivity. After immersion in a 5M KOH solution at 90°C for over 6,000 hours, the membrane experienced an ion loss rate of less than 3%, significantly enhancing its stability. The ultra-high stability anion exchange membrane exhibits excellent performance in applications such as anion exchange membrane water electrolysis and anion exchange membrane fuel cells.
[0119] Furthermore, the ultra-high stability anion exchange membrane described in the present invention addresses the defects of existing anion exchange membranes used in anion exchange membrane water electrolysis and anion exchange membrane fuel cells, namely the breakage of the aromatic skeleton and the degradation of quaternary ammonium salts. During actual application, they have high water absorption and high swelling rate, which greatly affect the long-term stability and efficiency of electrochemical devices. A more stable anion exchange membrane is designed and synthesized. By directly superacidizing the polymer monomers through a one-pot process, the synthesis steps of the membrane are simplified, the preparation process is simple, and it can match its large-scale production.
[0120] The ultra-high stability anion exchange membrane of the present invention is used to prepare fuel cell devices, and the device performance and stability are high. It shows high performance in anion exchange membrane water electrolysis and anion exchange membrane fuel cell devices. At the same time, at 80 ° C and 1 Acm -2 The anion exchange membrane water electrolysis device can operate stably for more than 3000 hours, with a voltage rise of less than 0.02mv / h, which exceeds most of the anion exchange membranes reported so far.
[0121] Furthermore, due to its excellent anion conductivity, chemical stability, mechanical properties and solubility, the suspended polyarylquinuclidine polymer described in the present invention can be used as an ionomer to be mixed with a catalyst, alcohol and water to form a catalyst ink, which can be used to prepare anion membranes or gas diffusion electrodes coated with a catalytic layer, and used in fields such as water electrolysis, fuel cells, CO2 reduction, metal-air batteries and liquid flow batteries to improve the stability and durability of device operation.
[0122] The suspended polyarylquinuclidine polymer provided by the present invention maintains the ring tension of the quinuclidine and can introduce a nitrogen-containing heterocycle into the polymer without using the strong electron-withdrawing group trifluoroacetyl, further improving the stability of the cationic functional group. Therefore, it can be used to prepare anion exchange membranes with ultra-high stability. In the anion exchange membrane structure described in the present invention, the water absorption and swelling rate of the polymer are regulated by adding a copolymerized hydrophobic monomer, thereby improving the mechanical strength of the polymer. By adding cross-linking groups, the polymer obtains a larger free volume and reduces membrane expansion, resulting in more obvious microphase separation within the polymer. The aggregation of cationic groups also helps to establish ion channels with lower transmission resistance. The polymer has been applied to alkaline water electrolysis and fuel cells, demonstrating that the polymer has excellent performance, which is of great significance for the industrial application of anion exchange membrane water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0123] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0124] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the I-type polyaryl quaternaryl quinine homopolymer prepared in Example 2;
[0125] Figure 2 1H NMR spectrum of the I-type polyaryl tri-quinine copolymer prepared in Example 4;
[0126] Figure 3 OH in Examples 3, 5 and 6 - Water absorption and swelling rate of anion exchange membrane at 80℃;
[0127] Figure 4 This is a diagram showing the anion exchange membrane of form I in Example 3;
[0128] Figure 5 The ionic conductivities of the OH-form anion exchange membrane and the QPAP membrane in Examples 3 and 7 at different temperatures;
[0129] Figure 6 The LSV curves of the anion exchange membrane in Experimental Example 3 at different temperatures (25, 40, 60, 80°C) in the alkaline electrolytic cell;
[0130] Figure 72 is the EIS curve of the anion exchange membrane in Experimental Example 3 at different temperatures (25, 40, 60, 80°C) in the alkaline electrolytic cell. DETAILED DESCRIPTION
[0131] The following examples are provided for a better understanding of the present invention and are not intended to limit the best mode of implementation. They do not limit the content and scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the scope of protection of the present invention.
[0132] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments is not specified, they are all commercially available conventional reagents.
[0133] Example 1
[0134] This embodiment provides a pendant polyaryl quaternaryl quinuclidine homopolymer, which is prepared by the following method:
[0135]
[0136] (1) In a 100 ml single-necked flask, p-terphenyl (1.1545 g, 5.0 mmol) and 4-quinine carboxaldehyde (0.8340 g, 6.0 mmol) were added to dichloromethane (5 mL). The mixture was stirred for 10 min in an ice-water bath and air atmosphere using a magnetic stirrer to obtain a light yellow mixed solution. TFSA (5.0 mL, 56.50 mmol) and TFA (0.5 mL, 6.50 mmol) were then added dropwise to the white mixed solution. After the addition was complete, the mixture was stirred for 3 h. During the reaction, the color of the solution changed from light yellow to red and finally to dark blue. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a yellow polymer.
[0137] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a suspended polyarylquinuclidine homopolymer;
[0138] Example 2
[0139] This embodiment provides an I-type pendant polyaryl quaternaryl quinuclidine homopolymer and a corresponding anion exchange membrane, wherein the polymer is prepared by the following method:
[0140]
[0141] (3) In a flask, the pendant polyarylquinuclidine homopolymer (2.0 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.455 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain type I pendant polyarylquinuclidine homopolymer.
[0142] (4) Will I - The polyaryl tetraquinine homopolymer (0.5 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast on a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 40 μm thick I - Type of polymer film;
[0143] (5) Will I - The polymer film was peeled off from the glass plate, immersed in 1M KOH solution, and ion exchanged at 60℃ for 12h to obtain OH - The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0144] Example 3
[0145] This embodiment provides an OH - A type suspended polyaryl four-quinuclidine homopolymer and a corresponding anion exchange membrane, wherein the polymer is prepared by the following method:
[0146]
[0147] (3) In a flask, polyaryl tetraquinine homopolymer (2.0 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.455 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Then, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain I - Type polyaryl tetraquinine homopolymer;
[0148] (4) Will I -The polyaryl tetraquinine homopolymer (0.5 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast on a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 40 μm thick I - Type of polymer film;
[0149] (5) Will I - The polymer film was peeled off from the glass plate, immersed in 1M KOH solution, and ion exchanged at 60℃ for 12h to obtain OH - The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0150] Example 4
[0151] This embodiment provides an OH-type pendant polyaryl tris-quinuclidine homopolymer (β-linked) and a corresponding anion exchange membrane, wherein the polymer is prepared by the following method:
[0152]
[0153] (1) In a 100 ml single-necked flask, p-terphenyl (1.1545 g, 5.0 mmol) and 3-quinine carboxaldehyde (0.8340 g, 6.0 mmol) were added to dichloromethane (5 mL). The mixture was stirred for 10 min in an ice-water bath and air atmosphere using a magnetic stirrer to obtain a light yellow mixed solution. TFSA (5.0 mL, 56.50 mmol) and TFA (0.5 mL, 6.50 mmol) were then added dropwise to the white mixed solution. After the addition was complete, the mixture was stirred for 3 h. During the reaction, the color of the solution changed from light yellow to red and finally to dark blue. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a yellow polymer.
[0154] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a polyaryl tetraquinine homopolymer;
[0155] (3) In a flask, the polyaryl tris-quinine copolymer (3.0 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.824 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain a quaternized polyaryl tris-quinine homopolymer.
[0156] (4) A quaternized polyaryl tris-quinine homopolymer (0.3 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast onto a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 30 μm thick I-type polymer film was obtained.
[0157] (5) Will I - The OH-type polymer membrane was peeled off from the glass plate and immersed in 1M KOH solution. Ion exchange was performed at 60°C for 12 h to obtain an OH-type membrane. The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0158] Finally, an OH-type polyaryl tris-quinine copolymer was obtained, and the obtained membrane was tested for water absorption and swelling rate;
[0159] Example 5
[0160] This embodiment provides an anion exchange membrane of a polyaryl tetraquinine copolymer with low swelling, low water absorption and high mechanical properties, wherein the anion exchange membrane is prepared by the following method:
[0161]
[0162] (1) In a 100 ml single-necked flask, p-terphenyl (1.1545 g, 5.0 mmol), 4-quinine carboxaldehyde (0.6255 g, 4.5 mmol) and trifluoroacetophenone (0.2612 g, 1.5 mmol) were added to dichloromethane (5 mL) and stirred with a magnetic stirrer in an ice-water bath under air atmosphere for 10 min to obtain a light yellow mixed solution. Then TFSA (5.0 mL, 56.50 mmol) was added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred for 6 h. During the reaction, the color of the solution changed from light yellow to red and finally to brown. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a light yellow polymer.
[0163] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a polyaryl tetraquinine copolymer;
[0164] (3) In a flask, the polyaryl tetraquinine copolymer (3.0 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.8244 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain the quaternized polyaryl tetraquinine copolymer.
[0165] (4) The quaternized polyaryl tetraquinine copolymer (0.6 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast onto a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 60 μm thick I-type polymer film was obtained.
[0166] (5) The I-type polymer film was peeled off from the glass plate and immersed in 1M KOH solution, and ion exchange was performed at 60°C for 12 h to obtain OH - The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0167] Finally, an OH-type polyaryl tetraquinine copolymer was obtained, and the obtained membrane was tested for water absorption and swelling rate;
[0168] Example 6
[0169] This embodiment provides an anion exchange membrane of a polyaryl tetraquinine copolymer having low swelling, low water absorption and high mechanical properties and having no electron-withdrawing groups in the main chain. The anion exchange membrane is prepared by the following method:
[0170]
[0171] (1) In a 100 ml single-necked flask, p-terphenyl (1.1545 g, 5.0 mmol), 4-quinine carboxaldehyde (0.6255 g, 4.5 mmol) and p-trifluoromethylbenzaldehyde (0.2612 g, 1.5 mmol) were added to dichloromethane (5 mL) and stirred with a magnetic stirrer in an ice-water bath under air atmosphere for 10 min to obtain a light yellow mixed solution. Then TFSA (5.0 mL, 56.50 mmol) was added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred for 6 h. During the reaction, the color of the solution changed from light yellow to red and finally to brown. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a light yellow polymer.
[0172] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a polyaryl tetraquinine copolymer;
[0173] (3) In a flask, the polyaryl tetraquinine copolymer (2.5 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.687 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain the quaternized polyaryl tetraquinine copolymer.
[0174] (4) The quaternized polyaryl tetraquinine copolymer (0.5 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast on a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 50 μm thick I - Type of polymer film;
[0175] (5) Will I - The OH-type polymer membrane was peeled off from the glass plate and immersed in 1M KOH solution. Ion exchange was performed at 60°C for 12 h to obtain an OH-type membrane. The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0176] Finally get OH - The polyaryl tetraquinine copolymer with no electron-withdrawing group in the main chain was prepared to obtain a membrane for water absorption and swelling rate testing;
[0177] Example 7
[0178] This embodiment provides an anion exchange membrane of a polyaryl tetraquinine copolymer having ultramicropores, wherein the anion exchange membrane is prepared by the following method:
[0179]
[0180] (1) In a 100 ml single-necked flask, p-terphenyl (0.5773 g, 2.5 mmol), m-terphenyl (0.5773, 2.5 mmol) and 4-quinine carboxaldehyde (0.8340 g, 6.0 mmol) were added to dichloromethane (5 mL) and stirred with a magnetic stirrer in an ice-water bath under air atmosphere for 10 min to obtain a light yellow mixed solution. Then TFSA (5.0 mL, 56.50 mmol) was added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred for 6 h. During the reaction, the color of the solution changed from light yellow to red and finally to brown. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a light yellow polymer.
[0181] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a polyaryl tetraquinine copolymer;
[0182] (3) In a flask, the polyaryl tetraquinine copolymer (2.5 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.687 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain the quaternized polyaryl tetraquinine copolymer.
[0183] (4) The quaternized polyaryl tetraquinine copolymer (0.45 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast on a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 45 μm thick I - Type of polymer film;
[0184] (5) Will I - The polymer film was peeled off from the glass plate, immersed in 1M KOH solution, and ion exchanged at 60℃ for 12h to obtain OH -The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0185] Finally get OH - The polyaryl tetraquinine copolymer having a main chain without electron-withdrawing groups was prepared to obtain a membrane for water absorption and swelling rate testing; Example 8
[0186] This embodiment provides a branched polyaryl tetraquinine polymer anion exchange membrane, which is prepared by the following method:
[0187]
[0188] (1) In a 100 ml single-necked flask, p-terphenyl (1.0968 g, 4.75 mmol), triphenylbenzene (0.0766 g, 0.25 mmol) and 4-quinine carboxaldehyde (0.8340 g, 6.0 mmol) were added to dichloromethane (5 mL) and stirred with a magnetic stirrer in an ice-water bath under air atmosphere for 10 min to obtain a light yellow mixed solution. Then TFSA (5.0 mL, 56.50 mmol) was added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred for 1 h. During the reaction, the color of the solution changed from white to red and finally to dark blue. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a light yellow polymer.
[0189] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a branched polyaryl tetraquinine polymer;
[0190] (3) In a flask, a branched polyaryl tetraquinine polymer (2.0 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.458 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain a quaternized, branched polyaryl tetraquinine polymer.
[0191] (4) The quaternized polymer (0.4 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast onto a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 40 μm thick I - Type of polymer film;
[0192] (5) Will I - The OH-type polymer membrane was peeled off from the glass plate and immersed in 1M KOH solution. Ion exchange was performed at 60°C for 12 h to obtain an OH-type membrane. The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0193] Finally, a branched anion exchange membrane was obtained, and the membrane was tested for conductivity;
[0194] Wherein, 5.0% is the percentage of the molar amount of triphenylbenzene to the total molar amount of triphenylbenzene and p-terphenyl;
[0195] Example 9
[0196] This embodiment provides a branched polyaryl tetraquinine polymer anion exchange membrane, which is prepared by the following method:
[0197]
[0198] (1) In a 100 ml single-necked flask, p-terphenyl (1.0968 g, 4.75 mmol), triptycene (0.1270 g, 0.25 mmol) and 4-quinine carboxaldehyde (0.8340 g, 6.0 mmol) were added to dichloromethane (5 mL) and stirred with a magnetic stirrer in an ice-water bath under air atmosphere for 10 min to obtain a light yellow mixed solution. TFSA (5.0 mL, 56.50 mmol) was then added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred for 1 h. During the reaction, the color of the solution changed from white to red and finally to dark blue. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a light yellow polymer.
[0199] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a branched polyaryl tetraquinine polymer;
[0200] (3) In a flask, a branched polyaryl tetraquinine polymer (2.8 g) was dissolved in DMSO (30 mL) and stirred at room temperature for 30 min. Then, K2CO3 (0.637 g) and iodomethane (5.0 mL) were added and stirred in the dark at room temperature for 12 h. Subsequently, the mixture was heated to 60 °C and stirred for 6 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain a quaternized, branched polyaryl tetraquinine polymer.
[0201] (4) The quaternized polymer (0.35 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast on a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 35 μm thick I - Type of polymer film;
[0202] (5) The I-type polymer film was peeled off from the glass plate and immersed in 1M KOH solution, and ion exchange was performed at 60°C for 12 h to obtain OH - The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0203] Finally, a branched anion exchange membrane was obtained, and the membrane was tested for conductivity;
[0204] Wherein, 5.0% is the percentage of the molar amount of triptycene to the total molar amount of triptycene and p-terphenyl;
[0205] Example 10
[0206] This embodiment provides a cross-linked polyaryl tetraquinine polymer anion exchange membrane, which is prepared by the following method:
[0207]
[0208] (1) In a 100 ml single-necked flask, p-terphenyl (0.5773 g, 2.5 mmol), m-terphenyl (0.5773, 2.5 mmol) and 4-quinine carboxaldehyde (0.8340 g, 6.0 mmol) were added to dichloromethane (5 mL) and stirred with a magnetic stirrer in an ice-water bath under air atmosphere for 10 min to obtain a light yellow mixed solution. Then TFSA (5.0 mL, 56.50 mmol) was added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred for 1 h. During the reaction, the color of the solution changed from white to red and finally to dark blue. The obtained viscous solution was poured into a 200 mL + 200 mL mixed solution of water and methanol to precipitate a light yellow polymer.
[0209] (2) The yellow polymer was crushed, the fragments were collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 h to neutralize the residual acid, and then washed three times with deionized water and dried in a vacuum oven at 80°C for 12 h to obtain a polyaryl tetraquinine homopolymer;
[0210] (3) In a flask, poly (aryl tetraquinine) homopolymer (2.5 g) was dissolved in DMSO (30 mL), and then propargyl bromide was added. The mixture was stirred at room temperature overnight, and then K2CO3 (0.637 g) and iodomethane (5.0 mL) were added. The mixture was stirred in the dark at room temperature for 12 h. 200 mL of ether was added to the resulting viscous solution. The yellow precipitate was filtered, rinsed with deionized water three times, and dried in a vacuum oven at 80 °C for 12 h to obtain a quaternized, cross-linked poly (aryl tetraquinine) polymer.
[0211] (4) The quaternized polymer (0.4 g) was dissolved in DMSO (15 mL). The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter and cast onto a flat, clean glass plate. The solution was then dried on a solvent evaporation heating table at 120 °C for 6 h. After the residual solvent was completely removed, a 40 μm thick I - Type of polymer film;
[0212] (5) Will I - The polymer film was peeled off from the glass plate, immersed in 1M KOH solution, and ion exchanged at 60℃ for 12h to obtain OH - The membrane was then washed three times with deionized water. To avoid CO2 contamination and carbonate formation, the membrane was preserved by immersing it in deionized water with nitrogen.
[0213] Finally, a cross-linked polyaryl tetraquinine polymer anion exchange membrane was obtained, and the membrane was tested for conductivity;
[0214] Experimental example
[0215] 1. NMR characterization
[0216] In this embodiment, the 1 prepared in Examples 2 and 4 is taken. - The I-type hanging polyaryl quinine homopolymer, the I-type polyaryl tetraquinine copolymer prepared in Examples 5, 6, and 7, the I-type branched polyaryl tetraquinine copolymer structure prepared in Examples 8 and 9, and the I-type cross-linked polyaryl tetraquinine copolymer prepared in Example 10 were characterized by nuclear magnetic resonance.
[0217] The reported new polymer structure 1 H NMR was measured using a Bruker 500MHz or 600MHz nuclear magnetic resonance spectrometer, using deuterated dimethyl sulfoxide (DMSO-d6, 99.9%-D) as a deuterated reagent. 1 The H spectrum was calibrated with the water peak (δ = 3.3 ppm) and DMSO-d6 (δ = 39.50 ppm).
[0218] 5-10 mg of the above polymer structure was dissolved in 0.8 mL of deuterated dimethyl sulfoxide and transferred to an NMR tube for testing.
[0219] Figure 1 I prepared in Example 2 - H NMR spectrum of polyaryl quaternary quinine homopolymer, 1 H NMR (500MHz, DMSO) δ7.92-7.48(m,12H),4.10(s,1H),3.59-3.30(m,6H),2.87(s,3H),2.08-1.71(m,6H).
[0220] Figure 2 I prepared in Example 4 - H NMR spectrum of polyaryl tri-quinine copolymer, 1 H NMR (500MHz, DMSO) δ7.92-7.48(m,12H),4.20(s,1H),3.70-3.20(m,6H),3.10-2.75(s,4H),2.24(s,1H),2.08-1.71(m,4H).
[0221] The H NMR spectrum of the I-type polyaryl tetraquinine copolymer with low swelling, low water absorption and high mechanical properties prepared in Example 5 is as follows: 1 H NMR (500MHz, DMSO) δ7.92-7.25(m,12H),4.10(s,0.85H),3.59-3.30(m,5H),2.87(s,2.55H),2.08-1.71(m,5H).
[0222] I prepared in Example 6 - The nuclear magnetic resonance hydrogen spectrum of the polyaryl tetraquinine copolymer with low swelling, low water absorption and high mechanical properties without electron-withdrawing groups, 1 H NMR (500MHz, DMSO) δ7.92-7.30(m,12H),4.10(s,0.86H),3.59-3.30(m,5H),2.87(s,2.6H),2.08-1.71(m,5H).
[0223] The nuclear magnetic resonance hydrogen spectrum of the I-type anion exchange membrane of the polyaryl tetraquinine copolymer with ultramicropores prepared in Example 7 is as follows: 1 HNMR (500MHz, DMSO) δ7.88-7.56(m,12H),4.10(s,1H),3.59-3.30(m,6H),2.87(s,3H),2.08-1.71(m,6H).
[0224] I prepared in Example 8 - The H NMR spectrum of the branched polyaryl tetraquinine polymer, 1 H NMR (500MHz, DMSO) δ7.89-7.19(m,12.16H),4.10(s,1H),3.59-3.30(m,6H),2.87(s,3H),2.08-1.71(m,6H).
[0225] I prepared in Example 9 - The H NMR spectrum of the branched polyaryl tetraquinine polymer, 1 H NMR (500MHz, DMSO) δ7.88-7.24(m,12.10H),4.10(s,1H),3.59-3.30(m,6H),2.87(s,3H),2.08-1.71(m,6H).
[0226] 2. Water absorption and swelling rate test
[0227] In this experimental example, the polyaryl tetraquinine homopolymer prepared in Example 3 and the polyaryl tetraquinine copolymer with low swelling, low water absorption and high mechanical properties prepared in Example 5 were prepared. - Type anion exchange membrane, the OH of the polyaryl tetraquinine copolymer with low swelling, low water absorption and high mechanical properties without electron-withdrawing group prepared in Example 6 - type anion exchange membrane, and the water absorption and swelling rate of the obtained membrane were tested.
[0228] Take the above OH -The anion exchange membranes were immersed in deionized water at different temperatures to achieve adsorption equilibrium. After the surface water was dried, the weight (Wwet) and length (Lwet) of the wet samples were measured. The membranes were then dried in a vacuum oven at 80°C for 24 hours to measure the weight (Wdry) of each membrane in the dry state. WU and SR were calculated using the following formulas. The calculation results are shown in the table below. Figure 4 .
[0229]
[0230] By the attached Figure 3 The results show that the OH of the polyaryl tetraquinine copolymer with low swelling and low water absorption prepared in this embodiment - The water absorption rate of the anion exchange membrane at 80°C (Example 3: 25.01%, Example 5: 15.21%, Example 6: 13.54%, <30%) and swelling rate (Example 3: 12.15%, Example 5: 6.54%, Example 6: 5.46%, <15%) are shown. It can be seen that the membrane of the present invention has low water absorption and swelling rate, guaranteed mechanical properties, and meets the established standards for anion exchange membrane water electrolysis hydrogen production electrolysis stack technology.
[0231] 3. Electrode performance test
[0232] This experimental example further conducted an electrochemical test on the performance of the electrode formed by the anion exchange membrane.
[0233] The anion exchange membrane prepared in Example 2, the anode catalyst NiFe catalyst, and the cathode catalyst platinum ruthenium carbon were assembled into a membrane electrode, installed in an anion exchange membrane electrolysis cell, and electrochemical testing was performed on an Autolab electrochemical workstation.
[0234] In this experimental example, the size of the anode and cathode catalysts is 1 cm×1 cm, and the electrolyte solution used in the anion exchange membrane electrolysis cell is 1 M KOH solution.
[0235] During the assembly process of the anion exchange membrane electrolyzer, the electrolyte solution is first heated to a specific temperature (40, 50, 60, 70, 80°C) by a heating rod, and then the heated electrolyte solution is transferred to the anode and cathode of the anion exchange membrane electrolyzer respectively by a peristaltic pump.
[0236] Before the electrochemical test, the electrolyte solution was circulated for 20 min to ensure a constant temperature of the entire test system. Subsequently, the entire electrolytic cell was activated by scanning the cyclic voltammetry (CV) curve. After the CV curve remained stable, a linear sweep voltammetry (LSV) test was performed.
[0237] Among them, the voltage range of the LSV test is 1.0-2.05V, the scan rate is 10mV / s, and the test temperature is (25, 40, 60, 80℃).
[0238] Subsequently, the two-electrode method was used to test the alternating current impedance (EIS) of the anion exchange membrane electrolytic cell at 80°C and 1.8V, wherein the impedance test frequency range was 100Khz-0.1Hz, the amplitude was 10mV, and the test temperature was (25, 40, 60, 80°C).
[0239] Finally, based on this, we also tested the operation of the entire device over time. It can be operated at 1Acm at 80℃. -2 The current density was 0.020 mV / h and the battery ran stably for 3000 h.
[0240] Figure 4 For the embodiment 3 I - Schematic diagram of an anion exchange membrane in the form of a 1.5-μm CMOS process.
[0241] Figure 5 OH in Examples 3 and 7 - The ionic conductivity of the anion exchange membrane and the QPAP membrane at different temperatures (25, 40, 50, 60, 70, 80 ° C) shows that the conductivity of the membrane of Example 3 at room temperature is 58.78 mS cm -1 The conductivity of the membrane of Example 7 at room temperature was 61.33 mS cm -1 Both are higher than the conductivity of QPAP membrane at the same temperature (20.60mS cm -1 ), and it can be seen that the OH in Examples 3 and 7 can be achieved at 80°C. - The ionic conductivity of the anion exchange membrane can reach 205.12 mS cm -1 and 210.98 mS cm -1 , indicating that the anion exchange membrane has high ionic conductivity and good application prospects. It is a high-performance anion exchange membrane that can match high-performance electrochemical devices.
[0242] Figure 6 The LSV curves of the polymer film in Example 3 at different temperatures (25, 40, 60, and 80°C) are shown. It can be seen that at 80°C: under an overpotential of 2V, the current density can reach 8.9A / cm 2 .
[0243] Figure 7The EIS curves are based on the polymer membrane in Example 3 at different temperatures (25, 40, 60, and 80°C). It can be seen that at 80°C, the electrochemical impedance is 0.035Ω, demonstrating high current density and low electrochemical impedance performance, outperforming most anion exchange membranes currently on the market.
[0244] 4. Anion exchange membrane fuel cell performance test
[0245] This experimental example tests the performance of an anion exchange membrane fuel cell prepared using the anion exchange membrane.
[0246] Preparation of membrane electrode: The polymer prepared in Synthesis Example 2 was used as the ion polymer binder for the catalyst layer. The anion exchange membrane was the membrane prepared in Example 3 with a thickness of 60 μm. The cathode and anode catalysts were platinum-carbon and platinum-ruthenium-carbon, respectively, with a platinum loading of 1 mg / cm 2 The mass ratio of catalyst to ion polymer was 4:1, and the membrane electrode was prepared by spraying method.
[0247] Battery assembly and performance test: The sealing gasket, graphite flow field, gold-plated current collector, insulating pad, heating end plate, etc. are assembled on both sides of the membrane electrode to obtain a single cell. The effective area of the electrode is 1cm 2 Humidified oxygen and hydrogen (purity greater than 99%, 100% humidification) were introduced into the cathode and anode of the battery respectively at a flow rate of 500 mL / min. After the battery operation stabilized, the current-voltage polarization curve of the battery was tested at 60°C. The open circuit voltage of the battery was 1.01 V and the maximum power density was 900 mW / cm 2 When the maximum power density is reached, the corresponding current density is 2250mA / cm 2 , the voltage is 0.4 V. The single cell maintains good operating stability within the test observation time interval.
[0248] Since the polymer described in the present invention has excellent anion conductivity, chemical stability, mechanical properties and solubility, its polymer solution can be used as an ionomer to be mixed with catalyst, alcohol and water to form catalyst ink, which is used to prepare anion membrane or gas diffusion electrode coated with a catalytic layer, thereby improving the stability and durability of device operation.
[0249] In summary, the present invention provides a type of suspended polyaryl quinuclidine polymer, which exhibits very good electrochemical performance and chemical stability. The skeleton structure of the all-carbon main chain does not contain electron-withdrawing groups in the main chain. At the same time, the main chain and the quinuclidine are not directly connected, which significantly reduces ion loss and further improves the chemical structure stability of the anion exchange membrane. Therefore, it can be used to prepare anion exchange membranes with ultra-high stability. In the anion exchange membrane of the structure described in the present invention, the water absorption and swelling rate of the polymer are regulated by adding copolymerized hydrophobic monomers or cross-linked structures to improve the mechanical strength of the polymer. By applying it to alkaline water electrolysis and fuel cells, it is proved that this type of polymer has very excellent performance, which is of great significance for the industrial application of anion exchange membrane water electrolysis.
[0250] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.
Claims
1. A quinuclidine-containing aldehyde monomer, characterized in that: The aldehyde monomer containing quinuclidine has a structure shown in the following formula (A): Wherein, L is selected from a single bond or a C6-C20 arylene group; R is selected from a single bond or a C1-C15 alkylene group.
2. The quinuclidine-containing aldehyde monomer according to claim 1, characterized in that L is selected from a single bond, phenylene, biphenylene, and naphthylene; Preferably, R is selected from a single bond or a C1-C10 straight chain alkylene group; Preferably, R is selected from a single bond, methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene; Preferably, the quinuclidine-containing aldehyde monomer is selected from one of the following structures:
3. Use of the quinuclidine-containing aldehyde monomer according to claim 1 in the preparation of anion exchange membranes.
4. A suspended polyarylquinuclidine polymer, characterized in that The pendant polyarylquinuclidine polymer comprises a unit having the following structure: Ar2 is a linear structural monomer containing at least two phenyl groups; The definitions of R and L are the same as those in claim 1; Preferably, the pendant polyarylquinuclidine polymer comprises units having the following structures: Wherein, Ar1 is a structural monomer containing at least 3 phenyl groups; R1 is a hydrophobic unit; The definitions of R and L are the same as those in claim 1; wherein the molar number of units of the structure of formula (P1) in the pendant polyarylquinuclidine polymer accounts for 50-99.9% of the total molar number of units of the structure of formula (P1), formula (P2) and / or formula (3) in the pendant polyarylquinuclidine polymer; Preferably, when the pendant polyarylquinuclidine polymer comprises structural units of formula (P1) and structural units of formula (P2), the pendant polyarylquinuclidine polymer may be a random copolymer, an alternating copolymer, a block copolymer or a graft copolymer; wherein the main chain of the graft copolymer is composed of structural units of formula (P2); Preferably, the pendant polyarylquinuclidine polymer has a structure as shown in the following formula (P): z, y n 、y m are the molar ratios of the units with the structures of formula (P2), formula (P1), and formula (P3) to the total structural units of the polymer, y n +y m +z=100%.
5. The pendant polyarylquinuclidine polymer according to claim 4, characterized in that z is 0-30%, y n 60%-100%, y m 0%-50%; Preferably, Ar1 is selected from at least one of the following structures: Preferably, the linear structural monomer containing at least two phenyl groups of Ar2 comprises 2-4 linearly connected substituted or unsubstituted benzene rings; wherein the substituent of the substituted benzene ring is selected from halogen, C1-C15 alkyl or C1-C15 alkoxy; Preferably, the benzene rings are connected by single bonds, unsaturated bonds, or fused bonds; Preferably, Ar2 comprises a diphenyl-substituted linear aromatic hydrocarbon; Preferably, Ar2 is selected from at least one of the following structures: Wherein, R2 is selected from hydrogen or C1-C10 alkyl; Preferably, R1 is selected from a hydrophobic unit comprising an electron-withdrawing group; Preferably, R1 is selected from substituted or unsubstituted aromatic ring hydrophobic units, substituted or unsubstituted saturated aliphatic hydrophobic units, substituted or unsubstituted ketone hydrophobic units, substituted or unsubstituted aldehyde hydrophobic units; Preferably, R1 is selected from a hydrophobic unit comprising at least one of trifluoromethyl, carbonyl, aldehyde, and pentafluorobenzene; Preferably, R1 is selected from one of the hydrophobic units having the following structure: Wherein, R3 and R6 are selected from hydrogen, halogen, C1-C10 alkyl or trifluoroacetyl; R4 is selected from C1-C10 alkyl; R5 is selected from hydrogen, C1-C10 alkyl or C6-C12 aryl.
6. The method for preparing the suspended polyarylquinuclidine polymer according to claim 4 or 5, characterized in that: The steps include: A structural monomer raw material containing at least three phenyl groups corresponding to Ar1, a linear structural monomer raw material containing at least two phenyl groups corresponding to Ar2, the aforementioned quinuclidine-containing aldehyde monomer, and a ketone or aldehyde raw material corresponding to the R1 hydrophobic unit are mixed in a first solvent, and then a polymerization reaction is carried out under the action of a first catalyst. The obtained viscous solution is added to a second solvent, and the precipitated product is collected, washed, and dried to obtain the pendant polyarylquinuclidine polymer; Wherein, the definitions of Ar1, Ar2, and R1 are the same as those in claim 4.
7. The preparation method according to claim 6, characterized in that The molar ratio of the structural monomer raw material containing at least 3 phenyl groups corresponding to Ar1 to the linear structural monomer raw material containing at least two phenyl groups corresponding to Ar2 is (0-50): (100-50); and / or, The molar ratio of the linear structure monomer raw material containing at least two phenyl groups corresponding to Ar2 to the quinuclidine-containing aldehyde monomer according to any one of claims 1 to 3 is 1:(1-1.5); and / or, The molar ratio of the ketone or aldehyde raw material corresponding to the R1 hydrophobic unit to the quinuclidine-containing aldehyde monomer according to any one of claims 1 to 3 is (0-0.4):1; and / or, The first solvent comprises at least one of dichloromethane, chloroform or tetrahydrofuran; and / or, The second solvent comprises at least one of ethyl acetate, methanol, ethanol, ether, tetrahydrofuran or acetone; and / or, The volume ratio of the first solvent to the second solvent is 1:(10-30); and / or, The amount of the quinuclidine-containing aldehyde monomer according to any one of claims 1 to 3 added to the first solvent is 10-22.5 mmol per 10-15 mL of the first solvent; and / or The washing step includes a step of adding a first alkali solution for washing and a step of adding a first alkali solution for washing; and / or, The first alkali solution comprises at least one of K2CO3, KOH, NaOH or NaHCO3 solution, preferably with a concentration of 0.5-2.0M; and / or, The drying step includes a step of vacuum drying at 60-80°C; and / or, The first catalyst includes trifluoroacetic acid and / or trifluoromethanesulfonic acid; wherein, Preferably, the first catalyst is trifluoroacetic acid, and the molar ratio of the trifluoroacetic acid to the quinuclidine-containing aldehyde monomer according to any one of claims 1 to 3 is (1-2):1; Preferably, the first catalyst is trifluoromethanesulfonic acid, and the molar ratio of the trifluoromethanesulfonic acid to the quinuclidine-containing aldehyde monomer according to any one of claims 1 to 3 is (10-20):
1.
8. A quaternized pendant polyarylquinuclidine polymer, characterized in that: The quaternized pendant polyarylquinuclidine polymer has a structure shown in the following formula (Q): Wherein, R7 is a quaternized group; Preferably, R7 is a C1-C20 alkyl group with a quaternized structure; Preferably, R7 is a C1-C20 alkyl group with a quaternized structure; Among them, Ar1, Ar2, R1, z, y n 、y m The definitions of , R, and L are the same as those in claim 4.
9. The method for preparing the quaternized suspended polyarylquinuclidine polymer according to claim 8, characterized in that: The method comprises the following steps: adding the dangling polyarylquinuclidine polymer according to any one of claims 4 to 5 or the dangling polyarylquinuclidine polymer prepared according to claim 6 to a third solvent, carrying out a quaternization reaction with a compound having an X-R7 structure under the action of a second catalyst, adding the viscous solution to a fourth solvent after the reaction, collecting the precipitate, washing it, and drying it to obtain the quaternized dangling polyarylquinuclidine polymer; wherein X represents a halogen, and R7 is as defined in claim 8; the dangling polyarylquinuclidine polymer according to any one of claims 4 to 5 or the dangling polyarylquinuclidine polymer prepared according to claim 6 is referred to as polymer P; Preferably, the polymer P and the compound having the structure X-R7 are added in a ratio of 1:(1-3), with the ratio unit being g:mL; and / or, The mass ratio of the polymer P to the second catalyst is (2-3):1; and / or, The second catalyst comprises K2CO3; and / or, The addition ratio of the polymer P and the third solvent is 1:(10-20), and the ratio unit is g:mL; and / or, The third solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; and / or, The fourth solvent comprises at least one of ethyl acetate, methanol, ethanol, acetone or diethyl ether; and / or, The volume ratio of the third solvent to the fourth solvent is 1:(6-10); and / or, The quaternization reaction temperature is 40-60° C. and the reaction time is 6-24 hours; and / or, The drying step includes vacuum drying at 60-80°C.
10. An ultra-high stability anion exchange membrane, characterized in that: The material of the anion exchange membrane is OH - Type anion exchange membrane, the ultra-high stability anion exchange membrane has a structure shown in the following formula (T): Among them, Ar1, Ar2, R1, z, y n 、y m The definitions of , R, and L are the same as those in claim 4.
11. The method for preparing the ultra-high stability anion exchange membrane according to claim 10, characterized in that: The steps include: The quaternized pendant polyarylquinuclidine polymer described in claim 8 or the quaternized pendant polyarylquinuclidine polymer prepared by the preparation method according to claim 9 is mixed with a fifth solvent to obtain a mixture, and the mixture is cast on the surface of a substrate to obtain an initial polymer film; then, the initial polymer film is immersed in a second alkaline solution to obtain the ultra-high stability anion exchange membrane, wherein the quaternized pendant polyarylquinuclidine polymer described in claim 8 or the quaternized pendant polyarylquinuclidine polymer prepared by the preparation method according to claim 9 is recorded as polymer Q; Preferably, the addition ratio of the polymer Q to the fifth solvent is 1:(10-100), and the addition ratio is g:mL; and / or, The fifth solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; and / or, The thickness of the high-stability anion exchange membrane is 20-60 μm; and / or, The second alkali solution includes NaOH and / or KOH solution; Preferably, the concentration of the second alkali solution is 0.5-2.0M; and / or, The temperature of the impregnation step is 25-80° C., and the impregnation time is 8-12 hours.
12. Use of the ultra-high stability anion exchange membrane according to claim 10 or the ultra-high stability anion exchange membrane prepared by the preparation method according to claim 11 in alkaline water electrolyzers, anion exchange membrane electrolyzers, alkaline fuel cells, flow batteries, and metal-air battery equipment.
13. Use of the pendant polyarylquinuclidine polymer according to claim 4 or 5 or the quaternized pendant polyarylquinuclidine polymer according to claim 8 in the preparation of anion exchange membranes, anion membranes coated with a catalytic layer, and gas diffusion electrodes.